A Pragmatic Case Study of Politeness in Instagram Comments: Insights from Medy Renaldy's Post - Fatih Akbar Rahmani (STAIRS: English Language Education Journal, 2025)
With the rapid growth of social media interactions, the challenge of maintaining respectful discourse has become increasingly urgent. Despite its importance, studies examining how politeness strategies function in Indonesian online contexts are scarce, leaving a gap in understanding both digital literacy and cultural sensitivity in public conversations. Therefore, this study investigates politeness strategies in digital discourse, focusing on responses to the term “Tuli” (deaf) in an Instagram post by Medy Renaldy. Using a qualitative approach and a single-case study design, this research analyzes approximately 100 comments employing Brown & Levinson’s politeness theory. The findings reveal that Medy predominantly uses positive politeness to foster harmony, even when faced with harsh criticism. In contrast, netizens frequently apply bald-on-record strategies, reflecting a lack of digital literacy and cultural sensitivity. Notably, external incentives, such as monetary offers, significantly influence shifts from impolite to polite behavior, demonstrating the pragmatism of digital politeness norms. This study highlights the importance of linguistic sensitivity and cultural awareness in fostering respectful online interactions. Practical recommendations include promoting digital literacy and integrating automated moderation tools to mitigate offensive behavior. These findings contribute to understanding the interplay between culture, politeness, and communication in digital environments, particularly within the Indonesian context.